기혼여성의 자연가족계획행위와 삶의 질에 관한 구조모형 - 최희정(Hee Jung Choi) (지역사회간호학회지, 2003)
Purpose: This study was to analyze the quality of life of married women practicing a natural family planning method based on given parameters in order to obtain some specific basic data for developing holistic programs to enhance the quality of life of married women practicing natural family planning. Methods: The subjects of this study were selected from married women who had been practicing natural family planning over two years. Data were collected from May 20 2001 to March 5 2002 using a structured questionnaire and interviews. The total number of subjects was 239. Collected data were analyzed using PC-SAS, which utilized descriptive statistics. In addition, LISREL 8.0 program was used to utilize covariance matrix. Results: The hypothetical model was reasonably fitted to commonly accepted data. Revision was required for the x2 value and RMR, and the model was revised by eliminating 6 paths. The revised model was fit well for commonly accepted data (x2 = 86.26, GFI = 0.97, NFl = 0.98, NNFI = 0.99, AGFI = 0.96, RMR = 0.02, CN= 422). Variables that influence the practice of natural family planning were communication of spouses, knowledge about natural family planning, self-efficacy and perceived benefits. Variables that control the quality of life were self-efficacy, internal health locus of control, attitude toward natural family planning, communication of spouses, perceived benefits and natural family planning behaviors. Conclusions: These findings prove that the quality of life of married women practicing natural family planning can be improved through developing programs that enhances communication of spouses, self-efficacy and perceived benefits.